Antibacterial and crease-resistant garment fabric and preparation process thereof

By using modified cotton fibers, electrospun fibers of polyacrylonitrile and polyurethane, and polylactic fibers containing silver nanowires, combined with materials such as citric acid modified titanium dioxide sol and nylon waste silk, the problem of cotton fabrics being prone to mold, deterioration and wrinkle, achieving significant improvements in antibacterial, anti-wrinkle and tensile fracture strength.

CN119711159APending Publication Date: 2025-03-28SHISHI HAOTIAN DRESS IND CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411883040.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Cotton fabrics are prone to mold and deterioration in humid environments, adsorbing bacteria, causing health problems, and are prone to wrinkle and deform during wearing. The existing anti-wrinkle finishing methods have problems such as environmental pollution, poor results or high costs.

Method used

Modified cotton fibers, electrospun fibers of polyacrylonitrile and polyurethane, and polylactic fibers containing silver nanowires are used to enhance the antibacterial, wrinkle-proof and tensile breaking strength of the fabric through the treatment of citric acid-modified titanium dioxide sol and nylon waste silk.

Benefits of technology

It significantly improves the antibacterial and wrinkle-proof effect of cotton fiber fabrics, enhances the tensile breaking strength and wrinkle-recovery ability of the fabric, and improves the antibacterial durability and wash resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005198645800000111
    Figure BDA0005198645800000111
Patent Text Reader

Abstract

The invention relates to the field of textile fabrics, and particularly discloses an antibacterial and crease-resistant garment fabric and a preparation process thereof. The antibacterial and crease-resistant garment fabric is prepared from modified cotton fibers and electrospun fibers of polyacrylonitrile and polyurethane according to the mass ratio of 1: (0.1-0.3): (0.3-0.5), and a preparation method of the polylactic acid fiber modified cotton fibers containing silver nanowires comprises the following steps that the cotton fibers are padded in finishing liquid and then dried and shaped, and pretreated cotton fibers are prepared; the pretreated cotton fibers are padded in the treating fluid and then dried and baked, and modified cotton fibers are prepared; the finishing liquid is prepared from the following raw materials: citric acid modified titanium dioxide sol, sodium hypophosphite, triethanolamine and deionized water; the treating fluid is prepared from the following raw materials: nylon waste silk, chitosan quaternary ammonium salt, N, N-dimethylformamide and alkaline silica sol. The garment fabric has the advantages of being good in antibacterial and crease-resistant effect, lasting in antibacterial effect and high in breaking strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of textile fabrics, and more specifically, to an antibacterial and wrinkle-resistant clothing fabric and a preparation process thereof. Background Art

[0002] Cotton fiber is an important textile fiber material. Its products are inexpensive, breathable, comfortable, biodegradable, safe and environmentally friendly, and are deeply favored by people. However, cotton fabrics are prone to mold and deterioration in a humid environment, adsorb bacteria, and are corroded by bacteria, causing health problems. In addition, the sweat and sebum excreted by the human body provide rich nutrition for fungal reproduction, causing bacterial growth. The growth of bacteria will not only cause cross-infection and spread diseases, produce odors, cause health problems, but also easily damage fibers. At the same time, when cotton fabrics are worn, they are subjected to external forces, and the cellulose molecular chains or their basic structural units will undergo relative displacement, the original hydrogen bonds will be disassembled, and new hydrogen bonds will be generated. When the external force is eliminated, creep will occur. When the external force is too large and the action time is too long, it is very easy to wrinkle and deform. Therefore, it is necessary to perform antibacterial and anti-wrinkle finishing on cotton fabrics. The development of antibacterial modified anti-wrinkle cotton fibers has excellent prospects.

[0003] Traditional anti-wrinkle finishing uses amino resins containing formaldehyde or potentially releasing formaldehyde, which causes great environmental pollution. In actual use, formaldehyde finishing agents such as 1,2,3,4-butanetetracarboxylic acid and citric acid either have poor finishing effects, severe yellowing of the fabric after finishing, and excessive strength loss, or are costly and difficult to be satisfactory. Cotton fabrics have poor antibacterial properties and are often finished by adding antibacterial finishing agents. However, due to the poor binding force between the antibacterial finishing agent and the fabric, the antibacterial properties of the fabric are low and it is not resistant to washing. At the same time, free antibacterial agents are potentially toxic to the human body. Therefore, the preparation of a cotton fiber fabric with significant antibacterial and anti-wrinkle effects meets market demand and has broad market value and application prospects. Summary of the invention

[0004] In order to improve the antibacterial and anti-wrinkle effects of cotton fiber fabrics and enhance the tensile breaking strength of cotton fiber fabrics, the present application provides an antibacterial and anti-wrinkle clothing fabric and a preparation process thereof.

[0005] In the first aspect, the present application provides an antibacterial and anti-wrinkle clothing fabric, which adopts the following technical solution: An antibacterial and wrinkle-resistant clothing fabric, comprising modified cotton fibers, electrospun fibers of polyacrylonitrile and polyurethane, and polylactic acid fibers containing silver nanowires in a mass ratio of 1:0.1-0.3:0.3-0.5; The method for preparing the modified cotton fiber comprises the following steps: The cotton fibers are dipped in a finishing liquid, dried, and shaped to obtain pretreated cotton fibers; The pretreated cotton fiber is immersed in a treatment solution, and then dried and baked to obtain modified cotton fiber; The finishing liquid comprises the following raw materials in parts by weight: 4-4.5 parts of citric acid modified titanium dioxide sol, 0.1-0.3 parts of sodium hypophosphite, 0.1-0.3 parts of triethanolamine, and 4.9-5.8 parts of deionized water; The treatment liquid comprises the following raw materials in parts by weight: 7.4-8.1 parts of nylon waste silk, 1.5-2.5 parts of chitosan quaternary ammonium salt, 52.6-59.4 parts of N,N-dimethylformamide and 40-45 parts of alkaline silica sol.

[0006] By adopting the above technical scheme, the finishing liquid contains citric acid modified titanium dioxide sol. When titanium dioxide is irradiated by ultraviolet light or visible light, the electrons on its surface will be excited to form highly reactive electron-hole pairs, which will react with water molecules and oxygen in the air to generate active substances such as hydroxyl free radicals and superoxide anions with strong oxidizing properties. These substances can destroy the cell walls and cell membranes of microorganisms such as bacteria and viruses, causing the death of microorganisms, thereby achieving the purpose of antibacterial. The citric acid contained in the citric acid modified titanium dioxide sol can undergo an esterification reaction with cotton fibers, and the citric acid is also connected to the hydroxyl groups of titanium dioxide by covalent bonds to form an interlaced network structure, thereby improving the negative interaction between titanium dioxide and cotton fabrics. Load fastness, reduce the shedding of titanium dioxide, thereby improving the antibacterial durability, sodium hypophosphite is used as a cross-linking reaction catalyst, which can increase the dehydration and cyclization of the carboxyl groups in the citric acid molecules and the esterification rate of the anhydride and cellulose, improve the number of anhydrides, and make more citric acid molecules react with the hydroxyl groups on the cotton fiber macromolecular chain, so that the anti-wrinkle recovery of the cotton fiber is improved, triethanolamine can neutralize the acidity of citric acid to prevent the fabric from suffering from excessive force loss, and citric acid has multiple hydroxyl groups, which can be well combined with titanium dioxide nanoparticles, indirectly anchoring it on the cellulose fiber, and has a certain wash resistance, in addition, the carboxyl groups in the citric acid molecules undergo esterification cross-linking reaction with the hydroxyl groups in the cellulose macromolecular chain, thereby enhancing the anti-wrinkle ability of the cotton fiber.

[0007] The pretreated cotton fiber is then treated with a treatment liquid. The nylon waste silk in the treatment liquid can be dissolved by DMF, and the nylon waste silk itself has certain elasticity and toughness. After heat treatment and baking, a layer of elastic film can be formed on the surface of the cotton fiber. When the cotton fiber is subjected to external force, the elastic film has a strong shape memory property and tends to pull the cotton fiber back to the state before the force is applied. Moreover, the silica component in the elastic film will block part of the hydroxyl groups on the cotton fiber, reducing the blocking effect of the hydroxyl groups forming hydrogen bonds at new positions, thereby further improving the wrinkle recovery performance. Moreover, under the action of titanium dioxide particles, the surface roughness of the pretreated cotton fiber increases, thereby improving the adhesion ability of the elastic film on the pretreated cotton fiber. In addition, the elastic film formed by the nylon waste silk can further protect the titanium dioxide sol, reduce the shedding of titanium dioxide particles, and improve the durability of the antibacterial ability of the cotton fiber. In addition, the chitosan quaternary ammonium salt has a strong antibacterial power, and can be combined with the elastic film formed by the nylon waste silk to further improve the antibacterial durability of the cotton fiber.

[0008] Polyacrylonitrile, also known as acrylic fiber, has excellent elasticity, warmth retention and strength. It has a high rebound rate, can maintain good recovery ability after elongation, and has a soft feel. Polyurethane is a thermoplastic elastomer with good flexibility and fatigue resistance. Mixed spinning with polyacrylonitrile can improve the wear-resistant disadvantage of polyacrylonitrile fiber. Therefore, the blended fiber of polyacrylonitrile and polyurethane can enhance the elasticity of the fabric, so that the cotton fabric can better recover to its original shape after being subjected to external force, thereby reducing the occurrence of wrinkles. Moreover, polyacrylonitrile fiber has high mechanical strength. The blended fiber can improve the overall strength of the fabric, making the fabric more durable and less prone to wrinkles due to external force. The flexibility and fatigue resistance of polyurethane can improve the surface morphology of the fabric, making the fabric smoother and reducing wrinkles caused by friction.

[0009] Silver nanowires are a new type of one-dimensional inorganic nanomaterial. Compared with nano silver ions, they have better viscosity, strong adhesion and toughness, and have excellent antibacterial properties. Silver nanowires are mixed with polylactic acid to obtain polylactic acid fibers containing silver nanowires, which enhances the antibacterial ability of polylactic acid fibers. Silver nanowires and polylactic acid are directly melt-spun into fibers, which improves the composite fastness of silver nanowires and polylactic acid fibers, increases washing fastness, and improves antibacterial durability. Polylactic acid fibers themselves have excellent physical properties, such as light weight, good resilience, strong wrinkle recovery ability, not easy to wrinkle, and certain iron-free performance. Therefore, blending polylactic acid fibers and cotton fibers can make full use of the wrinkle resistance of polylactic acid fibers, thereby improving the overall wrinkle resistance of blended fabrics. Polylactic acid fibers also have excellent properties such as environmental degradation, non-toxic anti-mite, antibacterial and health care, fire and moisture resistance, anti-allergy, and UV resistance.

[0010] Optionally, the preparation method of the polylactic acid fiber containing silver nanowires is as follows: Dispersing nanocellulose in deionized water to form a suspension with a concentration of 4-6 wt %; Adding silver nanowires to the suspension, adding cetylpyridinium bromide, stirring for 5-10 minutes, filtering and drying to obtain modified silver nanowires; The polylactic acid slices are dried and evenly mixed with the modified silver nanowires, and melt-spun to obtain polylactic acid fibers containing silver nanowires.

[0011] By adopting the above technical solution, after the suspension made of nanocellulose is mixed with the silver nanowires, the nanocellulose can be used as a dispersant. The hydrophilicity and high specific surface area of ​​the nanocellulose enable it to be adsorbed on the surface of the silver nanowires to prevent them from agglomerating, so that the silver nanowires are better dispersed in the polylactic acid matrix. After drying, the nanocellulose forms a protective layer on the silver nanowires. The hydrophobic groups of cetylpyridinium bromide can interact with the functional groups such as hydroxyl groups on the surfaces of the nanocellulose and the silver nanowires, thereby forming a hydrophobic layer on the surfaces of the two, so that the silver nanowires and the nanofibers are better dispersed. The cellulose is more evenly dispersed in the polylactic acid matrix, which improves the compatibility of silver nanowires with polylactic acid, increases the uniformity of the distribution of silver nanowires in polylactic acid fibers, and improves the mechanical strength of polylactic acid fibers. Moreover, cetylpyridinium bromide is a cationic surfactant, a quaternary ammonium compound, a typical organic antibacterial agent, and has excellent antibacterial activity. It can bond with the surface of silver nanowires through chemical adsorption to form a dense surfactant bilayer around the silver nanowires, thereby avoiding oxidation of the silver nanowires and having a strong stabilizing effect on the silver nanowires.

[0012] Optionally, the mass ratio of the silver nanowires to the polylactic acid slices is 0.1-0.2:1; The mass ratio of the silver nanowires, nanocellulose and cetylpyridinium bromide is 1:0.8-1:0.6-1.

[0013] By adopting the above technical scheme, an appropriate amount of silver nanowires is added to the polylactic acid slices, which not only improves the antibacterial ability of the polylactic acid fiber, but also does not affect the tensile and fracture strength of the polylactic acid; and nanocellulose and cetylpyridinium bromide are mixed with silver nanowires in appropriate amounts to improve the blending uniformity of the silver nanowires and the polylactic acid slices during melt spinning.

[0014] Optionally, the electrospun fibers of polyacrylonitrile and polyurethane are prepared by the following method: Add polyacrylonitrile to DMF, stir and dissolve to obtain a base solution with a concentration of 10 wt%, add polyurethane, stir and dissolve to obtain a spinning solution; The spinning solution is subjected to electrospinning and vacuum drying for 10-12 hours to obtain a nanofiber membrane; Dissolving chitosan with acetic acid solution to prepare a base solution with a concentration of 1-1.5 wt%, adding a penetrant and nano zinc oxide to the base solution, and ultrasonicating for 10-20 minutes to prepare an impregnation solution; The nanofiber membrane is placed in the impregnation solution, and rolled twice to a rolling rate of 80-85%, and then dried at 75-80°C.

[0015] By adopting the above technical scheme, the spinning solution formed by polyacrylonitrile and polyurethane is electrospun to obtain a nanofiber membrane with a smooth surface and a porous structure, and the pores can maintain a high degree of connectivity. In addition, the introduction of polyurethane into polyacrylonitrile can improve the tensile strength of the electrospun fiber, thereby enhancing the breaking strength of the clothing fabric. The nanofiber membrane is impregnated with an impregnation solution formed by nano zinc oxide, chitosan and a penetrant. Nano zinc oxide has many surface active centers, strong adsorption capacity and strong catalytic properties. Nano zinc oxide can penetrate into the pores of the nanofiber membrane and A protective film is formed on the surface of the nanofiber membrane to prevent the sliding of some macromolecular chains. The adhesion of chitosan increases the fastness of zinc oxide on the surface of the nanofiber membrane, while also improving the feel of the electrospun fibers. In addition, chitosan contains a large number of amino and hydroxyl groups. The amino groups can adsorb bacteria and combine with the anions of the cell wall to hinder the biosynthesis of the cell wall and achieve an antibacterial effect. Chitosan can also diffuse to a certain extent inside the fiber, changing the internal structure of the fiber and combining more closely with the fiber to limit the slippage between fiber molecules, thereby increasing resilience and improving wrinkle recovery.

[0016] Optionally, the mass ratio of polyacrylonitrile to polyurethane is 2.5-3:1; The mass ratio of the chitosan, the penetrant and the nano zinc oxide is 1:0.1-0.5:1-2.

[0017] By adopting the above technical scheme, the dosage of polyacrylonitrile and polyurethane is appropriate, and a nanofiber membrane with uniform diameter and smooth surface can be obtained. If the dosage of polyurethane is too much, the diameter of the nanofiber will be uneven and the mechanical capacity will decrease. The dosage ratio of chitosan, penetrant and nano zinc oxide can make the nano zinc oxide fully penetrate and fill the surface of the nanofiber membrane. Chitosan can make the nano zinc oxide have a strong load fastness and a high antibacterial ability.

[0018] Optionally, the penetrant is selected from at least one of sodium alkyl sulfonate, sodium secondary alkyl sulfate, sodium isooctyl polyoxyethylene ether phosphate, sulfated castor oil, and phosphate compounds.

[0019] By adopting the above technical solution, the penetrant has a significant softening effect, can improve the feel of the electrospun fiber, and increase the permeability of nano zinc oxide and chitosan, thereby forming a breathable, antibacterial and high-breaking strength film inside and on the surface of the electrospun fiber.

[0020] Optionally, the preparation method of the citric acid modified titanium dioxide sol is as follows: by weight, 1-2 parts of citric acid, 13-16 parts of anhydrous ethanol and 1-2 parts of butyl titanate are mixed evenly to prepare solution A, and 6-12 parts of deionized water, 0.075-0.15 parts of concentrated hydrochloric acid and 7-8 parts of anhydrous ethanol are mixed evenly to prepare solution B; Solution B was added into solution A and stirred evenly at room temperature to obtain a citric acid-modified titanium dioxide sol.

[0021] By adopting the above technical scheme, citric acid is a hydroxy polyacid, which has excellent ability to form coordination bonds with transition metal ions containing potential coordination bonds. At a suitable pH, the carboxyl anion is ionized and reacts with Ti produced by hydrolysis of butyl titanate. 4+ Combined with the above, the steric hindrance effect of the product will ease the hydrolysis reaction, and sol particles are formed after hydrolysis and polycondensation of butyl titanate.

[0022] Optionally, the rolling rate during the padding of the finishing liquid is 70-75%, the drying temperature is 50-55° C., the drying time is 3-5 min, the shaping temperature is 150-160° C., and the shaping time is 3-5 min; The processing liquid has a rolling rate of 80-85%, a drying temperature of 50-55° C., a drying time of 3-5 minutes, a baking temperature of 120-130° C., and a baking time of 3-5 minutes.

[0023] By adopting the above technical scheme, with appropriate rolling ratio, drying temperature and time, and shaping temperature and time, the cotton fibers treated with the finishing liquid have a better shaping effect, reduce their shrinkage, and increase the load fastness between the finishing liquid and the cotton fibers.

[0024] In a second aspect, the present application provides a method for preparing an antibacterial and anti-wrinkle clothing fabric, which adopts the following technical scheme: A method for preparing an antibacterial and anti-wrinkle clothing fabric, comprising the following steps: The modified cotton fiber, electrospun fiber of polyacrylonitrile and polyurethane and polylactic acid fiber containing silver nanowires are mixed, carded, drawn, roved, spun, wound and woven to make fabrics.

[0025] By adopting the above technical scheme, modified cotton fibers and other raw materials can be made into clothing fabrics with good wear resistance and warmth retention, lighter and softer texture, and smooth and delicate surface through mixing, combing and other processes.

[0026] Optionally, during the weaving, the warp yarn count is 150-180 needles / cm, the weft yarn count is 200-220 needles / cm; the warp knitting speed is 600-800m / min, the fabric thickness is 0.5-1.5mm, and the gram weight is 50-300g / m2 .

[0027] By adopting the above technical solution, when weaving the clothing fabric, by controlling the warp and weft yarn counts, warp knitting speed, fabric thickness and gram weight during weaving, the finished fabric can be made more delicate and smooth, feel lighter and softer, be more comfortable to wear, and have better breathability.

[0028] In summary, this application has the following beneficial effects: 1. Since the present application adopts modified cotton fiber, electrospun fiber of polyacrylonitrile and polyurethane and polylactic acid fiber containing silver nanowires as raw materials for clothing fabrics, and the modified cotton fiber is first impregnated with a finishing solution containing citric acid-modified titanium dioxide sol, and then impregnated with a treatment solution containing nylon waste silk and chitosan quaternary ammonium salt, the citric acid-modified titanium dioxide solution can improve the antibacterial ability of the cotton fiber and improve the anti-wrinkle effect, the chitosan quaternary ammonium salt further increases the antibacterial property, and the nylon waste silk can increase the load fastness of titanium dioxide particles and chitosan quaternary ammonium salt, and increase the antibacterial durability. At the same time, the finishing solution and the treatment solution can also improve the anti-wrinkle effect of the cotton fiber; the electrospun fiber of polyacrylonitrile and polyurethane can effectively improve the breaking strength loss of the cotton fiber after finishing and treatment, improve the breaking strength of the clothing fabric, and increase the anti-wrinkle force, and the polylactic acid fiber containing silver nanowires can not only increase the antibacterial ability of the clothing fabric, but also improve its breaking strength and enhance the anti-wrinkle recovery ability.

[0029] 2. In the present application, nanocellulose and cetylpyridinium bromide are preferably used to pretreat the silver nanowires, which can improve the dispersion uniformity of the silver nanowires and the polylactic acid chips when they are blended and melted, and reduce the effect of the silver nanowires on the tensile strength of the polylactic acid fibers.

[0030] 3. In the present application, it is preferred to use an impregnation solution formed by nano zinc oxide, chitosan and a penetrant to impregnate the polyacrylonitrile and polyurethane mixed electrospinning product, which can make the electrospun fibers of polyacrylonitrile and polyurethane have certain antibacterial and lasting antibacterial properties, and can further improve the breaking strength and anti-wrinkle effect of clothing fabrics. DETAILED DESCRIPTION

[0031] The following examples further illustrate the present application in detail.

[0032] Preparation example of modified cotton fiber Preparation Example 1: (1) Cotton fiber is twice dipped and twice rolled in a finishing liquid, and then dried and shaped to obtain pretreated cotton fiber, each rolling rate is 75%, the drying temperature is 55°C, the drying time is 3 min, the shaping temperature is 160°C, and the shaping time is 3 min. The finishing liquid is prepared by mixing the following raw materials: 4.5 kg of citric acid modified titanium dioxide sol, 0.3 kg of sodium hypophosphite, 0.3 kg of triethanolamine and 4.9 kg of deionized water. The citric acid modified titanium dioxide is prepared by the following method: 1 kg of citric acid, 13 kg of anhydrous ethanol and 1 kg of butyl titanate are mixed uniformly to obtain solution A, 6 kg of deionized water, 0.075 kg of concentrated hydrochloric acid and 7 kg of anhydrous ethanol are mixed uniformly to obtain solution B, and solution B is added to solution A, and stirred at room temperature to obtain citric acid modified titanium dioxide sol; (2) The pretreated cotton fiber is immersed and rolled twice in the treatment liquid, and then dried and baked to obtain modified cotton fiber. The rolling rate each time is 85%, the drying temperature is 55°C, the drying time is 3 minutes, the baking temperature is 130°C, and the baking time is 3 minutes. The treatment liquid is prepared by mixing the following raw materials: 7.4 kg nylon waste silk, 2.5 kg chitosan quaternary ammonium salt, 52.6 kg N, N-dimethylformamide and 40 kg alkaline silica sol. The alkaline silica sol is selected from Shandong Better New Materials, model HC4020, and the chitosan quaternary ammonium salt is selected from Yuanye Biotechnology, product number S26618.

[0033] Preparation Example 2: (1) Cotton fiber is twice dipped and twice rolled in a finishing liquid, and then dried and shaped to obtain pretreated cotton fiber, each rolling rate is 70%, the drying temperature is 50°C, the drying time is 5 min, the shaping temperature is 150°C, and the shaping time is 5 min. The finishing liquid is prepared by mixing the following raw materials: 4 kg of citric acid-modified titanium dioxide sol, 0.1 kg of sodium hypophosphite, 0.1 kg of triethanolamine and 5.8 kg of deionized water. The citric acid-modified titanium dioxide is prepared by the following method: 2 kg of citric acid, 16 kg of anhydrous ethanol and 2 kg of butyl titanate are mixed uniformly to obtain solution A, 12 kg of deionized water, 0.015 kg of concentrated hydrochloric acid and 8 kg of anhydrous ethanol are mixed uniformly to obtain solution B, and solution B is added to solution A, and stirred at room temperature to obtain citric acid-modified titanium dioxide sol; (2) The pretreated cotton fiber is immersed and rolled twice in the treatment liquid, and then dried and baked to obtain modified cotton fiber. The rolling rate each time is 80%, the drying temperature is 50°C, the drying time is 5 min, the baking temperature is 120°C, and the baking time is 5 min. The treatment liquid is prepared by mixing the following raw materials: 8.1 kg nylon waste silk, 1.5 kg chitosan quaternary ammonium salt, 59.4 kg N, N-dimethylformamide and 45 kg alkaline silica sol. The alkaline silica sol is selected from Shandong Better New Materials, model HC4020, and the chitosan quaternary ammonium salt is selected from Yuanye Biotechnology, product number S26618.

[0034] Preparation Example 3: The difference from Preparation Example 1 is that no treatment liquid is used for impregnation, and the pretreated cotton fiber is the modified cotton fiber.

[0035] Preparation Example 4: The difference from Preparation Example 1 is that no nylon waste is added to the treatment solution.

[0036] Preparation Example 5: The difference from Preparation Example 1 is that the finishing liquid impregnation treatment is not adopted, and the cotton fiber is directly impregnated and pressed twice with the treatment liquid. The other parameters are the same as those of Preparation Example 1.

[0037] Preparation Example 6: The difference from Preparation Example 1 is that the titanium dioxide sol used is not modified by citric acid, and the titanium dioxide sol is selected from Jingrui New Materials, model VK-TA33, and the average particle size is 10nm.

[0038] Preparation Examples 7-10 of Polylactic Acid Fibers Containing Silver Nanowires Preparation Example 7: 10 g of nanocellulose was dispersed in deionized water to form a suspension with a concentration of 6 wt %; 10 g of silver nanowires were added to the suspension, and 10 g of cetylpyridinium bromide was added. After stirring for 10 min, the mixture was filtered and dried to obtain modified silver nanowires. The diameter of the silver nanowires was 60 nm and the length was 20 μm. 100 g of polylactic acid chips were dried at 65°C for 3 h, heated to 100°C, dried to a water content of less than 0.005%, and then mixed evenly with modified silver nanowires and melt-spun. The spinning temperature was 195°C, the spinning speed was 1000 m / min, the stretching multiple was 3, the stretching temperature was T1 / T2 / T3=72°C / 80°C / 82°C, and the polylactic acid chips were selected from Nature Works, USA, model 6202D.

[0039] Preparation Example 8: 16 g of nanocellulose was dispersed in deionized water to form a suspension with a concentration of 4 wt%; 20 g of silver nanowires were added to the suspension, and 12 g of cetylpyridinium bromide was added. After stirring for 10 min, the mixture was filtered and dried to obtain modified silver nanowires. The diameter of the silver nanowires was 60 nm and the length was 20 μm. 100 g of polylactic acid chips were dried at 65°C for 3 h, heated to 100°C, dried to a water content of less than 0.005%, and then mixed evenly with modified silver nanowires and melt-spun. The spinning temperature was 195°C, the spinning speed was 1000 m / min, the stretching multiple was 3, the stretching temperature was T1 / T2 / T3=72°C / 80°C / 82°C, and the polylactic acid chips were selected from Nature Works, USA, model 6202D.

[0040] Preparation Example 9: The difference from Preparation Example 7 is that cetylpyridinium bromide is not added.

[0041] Preparation Example 10: The difference from Preparation Example 7 is that nanocellulose and cetylpyridinium bromide are not added, and the preparation is made by the following method: 100 g of polylactic acid chips are dried at 65°C for 3 h, heated to 100°C, and dried to a water content of less than 0.005%, and then mixed evenly with silver nanowires, melt-spun, the spinning temperature is 195°C, the spinning speed is 1000 m / min, the stretching multiple is 3, the stretching temperature T1 / T2 / T3=72°C / 80°C / 82°C, the mass ratio of polylactic acid chips to silver nanowires is 1:0.1, and the polylactic acid chips are selected from Nature Works, USA, model 6202D.

[0042] Preparation of electrospun fibers of polyacrylonitrile and polyurethane Examples 11-15 Preparation Example 11: 10 g of polyacrylonitrile was added to MDF, the temperature was raised to 50° C., and the mixture was stirred until completely dissolved to obtain a base solution with a concentration of 10 wt%. Polyurethane was added and stirred to dissolve at 50° C. to obtain a spinning solution. The mass ratio of polyacrylonitrile to polyurethane was 3:1. The Mw of polyacrylonitrile was 150,000. The polyurethane was selected from Shanghai Jizhi Biochemical Technology Co., Ltd. with a product number of P12660. The polyurethane was selected from Bayer of Germany with a model number of 3685AU. The spinning solution was electrospun and then vacuum dried for 12 hours to obtain a nanofiber membrane. The spinning voltage was 70 kV, the relative humidity was 40%, the receiving distance was 220 mm, and the spinning speed was 200 mm / s. Dissolve 10g of chitosan in acetic acid solution to prepare a base solution with a concentration of 1.5wt%, add 5g of penetrant and 20g of nano zinc oxide to the base solution, and disperse by ultrasonic for 20min to prepare an impregnation solution, wherein the penetrant is sodium dodecyl sulfate; The nanofiber membrane was placed in the impregnation solution, and the mixture was dipped twice and rolled twice, with the rolling rate being 85%. The mixture was dried at 80° C. for 5 minutes to obtain electrospun fibers of polyacrylonitrile and polyurethane.

[0043] Preparation Example 12: 10 g of polyacrylonitrile was added to MDF, the temperature was raised to 50° C., and the mixture was stirred until completely dissolved to obtain a base solution with a concentration of 10 wt%. Polyurethane was added and stirred to dissolve at 50° C. to obtain a spinning solution. The mass ratio of polyacrylonitrile to polyurethane was 2.5:1. The Mw of polyacrylonitrile was 150,000. The polyurethane was selected from Shanghai Jizhi Biochemical Technology Co., Ltd. with a product number of P12660. The polyurethane was selected from Bayer of Germany with a model number of 3685AU. The spinning solution was electrospun and then vacuum dried for 12 hours to obtain a nanofiber membrane. The spinning voltage was 70 kV, the relative humidity was 40%, the receiving distance was 220 mm, and the spinning speed was 200 mm / s. Dissolve 10g of chitosan in acetic acid solution to prepare a base solution with a concentration of 1wt%, add 1g of penetrant and 10g of nano zinc oxide to the base solution, and ultrasonically disperse for 20min to prepare an impregnation solution, wherein the penetrant is sodium dodecyl sulfate; The nanofiber membrane was placed in the impregnation solution, and the mixture was dipped twice and rolled twice, with the rolling rate being 80%. The mixture was dried at 70° C. for 8 minutes to obtain electrospun fibers of polyacrylonitrile and polyurethane.

[0044] Preparation Example 13: The difference from Preparation Example 11 is that no nano zinc oxide is added.

[0045] Preparation Example 14: The difference from Preparation Example 11 is that an equal amount of deionized water is used to replace the base liquid.

[0046] Preparation Example 15: The difference from Preparation Example 11 is that nano zinc oxide, chitosan and penetrant are not added, and the following method is used to prepare: 10g of polyacrylonitrile is added to MDF, the temperature is raised to 50°C, and stirred until completely dissolved to prepare a base liquid with a concentration of 10wt%, polyurethane is added, and stirred and dissolved at 50°C to prepare a spinning solution, the mass ratio of polyacrylonitrile to polyurethane is 3:1, the Mw of polyacrylonitrile is 150000, selected from Shanghai Jizhi Biochemical Technology, the product number is P12660, and the polyurethane is selected from Bayer, Germany, the model is 3685AU; The spinning solution was subjected to electrostatic spinning and then vacuum dried for 12 hours to obtain electrospun fibers. The spinning voltage was 70 kV, the relative humidity was 40%, the receiving distance was 220 mm, and the spinning speed was 200 mm / s. Example

[0047] Example 1: An antibacterial and wrinkle-resistant clothing fabric, comprising modified cotton fiber, polyacrylonitrile and polyurethane blended fiber and polylactic acid fiber containing silver nanowires in a mass ratio of 1:0.3:0.5, the modified cotton fiber is made by Preparation Example 1, the polylactic acid fiber containing silver nanowires is made by Preparation Example 7, and the polyacrylonitrile and polyurethane blended fiber is made by Preparation Example 11.

[0048] The preparation process of the antibacterial and wrinkle-resistant clothing fabric comprises the following steps: Modified cotton fiber, electrospun fiber of polyacrylonitrile and polyurethane and polylactic acid fiber containing silver nanowires are mixed, carded, drawn, roving, spun, wound and woven to make fabrics. The warp yarn count is 150 needles / cm and the weft yarn count is 200 needles / cm during weaving. The warp knitting speed is 600m / min, the fabric thickness is 0.5mm, and the weight is 50g / m 2 .

[0049] Example 2: An antibacterial and wrinkle-resistant clothing fabric, comprising modified cotton fiber, polyacrylonitrile and polyurethane blended fiber and polylactic acid fiber containing silver nanowires in a mass ratio of 1:0.1:0.3, the modified cotton fiber is made by Preparation Example 2, the polylactic acid fiber containing silver nanowires is made by Preparation Example 8, and the polyacrylonitrile and polyurethane blended fiber is made by Preparation Example 12.

[0050] The preparation process of the antibacterial and wrinkle-resistant clothing fabric comprises the following steps: The modified cotton fiber, electrospun fiber of polyacrylonitrile and polyurethane and polylactic acid fiber containing silver nanowires are mixed, carded, drawn, roving, spun, wound and woven to make fabrics. The warp yarn count is 180 needles / cm and the weft yarn count is 220 needles / cm during weaving. The warp knitting speed is 800m / min, the fabric thickness is 1.5mm, and the weight is 300g / m 2 .

[0051] Example 3: An antibacterial and wrinkle-resistant clothing fabric, comprising modified cotton fiber, polyacrylonitrile and polyurethane blended fiber and polylactic acid fiber containing silver nanowires in a mass ratio of 1:0.1:0.5, the modified cotton fiber is made by Preparation Example 1, the polylactic acid fiber containing silver nanowires is made by Preparation Example 8, and the polyacrylonitrile and polyurethane blended fiber is made by Preparation Example 11.

[0052] The preparation process of the antibacterial and wrinkle-resistant clothing fabric comprises the following steps: The modified cotton fiber, electrospun fiber of polyacrylonitrile and polyurethane and polylactic acid fiber containing silver nanowires were mixed, carded, drawn, roving, spun, wound and woven to make fabrics. The warp yarn count was 170 needles / cm and the weft yarn count was 210 needles / cm during weaving. The warp knitting speed was 700m / min, the fabric thickness was 1.0mm, and the weight was 200g / m 2 .

[0053] Example 4: An antibacterial and wrinkle-resistant clothing fabric, which is different from Example 1 in that the polylactic acid fiber containing silver nanowires is made from Preparation Example 9.

[0054] Example 5: An antibacterial and wrinkle-resistant clothing fabric, which differs from Example 1 in that the polylactic acid fiber containing silver nanowires is made from Preparation Example 10.

[0055] Example 6: An antibacterial and wrinkle-resistant clothing fabric, which is different from Example 1 in that the electrospun fibers of polyacrylonitrile and polyurethane are made from Preparation Example 13.

[0056] Example 7: An antibacterial and wrinkle-resistant clothing fabric, which is different from Example 1 in that the electrospun fibers of polyacrylonitrile and polyurethane are made from Preparation Example 14.

[0057] Example 8: An antibacterial and wrinkle-resistant clothing fabric, which is different from Example 1 in that the electrospun fibers of polyacrylonitrile and polyurethane are made from Preparation Example 15.

[0058] Comparative Example Comparative Example 1: An antibacterial and wrinkle-resistant clothing fabric, which is different from Example 1 in that the modified cotton fiber is made from Preparation Example 3.

[0059] Comparative Example 2: An antibacterial and wrinkle-resistant clothing fabric, which is different from Example 1 in that the modified cotton fiber is made from Preparation Example 4.

[0060] Comparative Example 3: An antibacterial and wrinkle-resistant clothing fabric, which is different from Example 1 in that the modified cotton fiber is made from Preparation Example 5.

[0061] Comparative Example 4: An antibacterial and wrinkle-resistant clothing fabric, which is different from Example 1 in that the modified cotton fiber is made from Preparation Example 6.

[0062] Comparative Example 5: An antibacterial and wrinkle-resistant clothing fabric, which differs from Example 1 in that electrospun fibers of polyacrylonitrile and polyurethane are not added.

[0063] Comparative Example 6: An antibacterial and wrinkle-resistant clothing fabric, which differs from Example 1 in that electrospun fibers of polyacrylonitrile and polyurethane and polylactic acid fibers containing silver nanowires are not added.

[0064] Comparative Example 7: An antibacterial and wrinkle-resistant clothing fabric, which is different from Example 1 in that the cotton fiber is not modified.

[0065] Comparative Example 8: A cotton fabric is made of cotton fiber through carding, drawing, roving, spun yarn, winding and weaving. The warp yarn count is 150 needles / cm and the weft yarn count is 200 needles / cm during weaving. The warp knitting speed is 600m / min, the fabric thickness is 0.5mm, and the weight is 50g / m 2 .

[0066] Performance testing 1. Fabric breaking strength: According to the national standard GB / T 3923.1-1997 "Tensile properties of textile fabrics Part 1: Determination of breaking strength and breaking elongation by strip method", take 3 pieces of fabric with a length of 30 cm and a width of 5 cm, and use the edge yarn method to make the width of the sample 5 cm. Test it on a YG026 electronic fabric strength testing machine. The tensile length is preset to 20 cm, the tensile speed is 100 mm / min, and three parallel tests are performed, and the average value is recorded.

[0067] 2. Wrinkle recovery angle: It is carried out in accordance with the horizontal method in GB / T 3819-1997 "Determination of recovery angle of crease recovery of textile fabrics". In the YG(B)541D fabric wrinkle elasticity tester (Wenzhou Darong Textile Instrument Co., Ltd.), only the dry slow-elastic wrinkle recovery angle (warp + weft) is recorded.

[0068] 3. Antibacterial property: The fabric was placed in a standard atmospheric environment with a temperature of 21°C and a relative humidity of 65% for humidity adjustment. The antibacterial property of the fabric was tested with reference to GB / T20944.3-2008 "Evaluation of Antibacterial Properties of Textiles". The sample size was 30cm×30cm. It was divided into a pre-wash test and a hang-to-dry test after washing 50 times. The test bacteria were Staphylococcus aureus, Escherichia coli and Candida albicans. The antibacterial rate was used to evaluate the antibacterial performance of the antibacterial solution against Staphylococcus aureus, Escherichia coli and Candida albicans.

[0069] Table 1 Performance test of antibacterial and anti-wrinkle clothing fabrics Combined with the dosage table of modified cotton fiber, electrospun fiber of polyacrylonitrile and polyurethane, and polylactic acid fiber containing silver nanowires in Examples 1-3, the preparation example selection and the test data in Table 1, it can be seen that the clothing fabrics prepared in Examples 1-3 have increased breaking strength, strong wrinkle recovery, sufficient initial antibacterial power, and still show excellent antibacterial performance after multiple washings, indicating that the prepared antibacterial and anti-wrinkle clothing fabrics have high anti-wrinkle ability and lasting antibacterial properties.

[0070] Compared with Example 1, Example 4 uses the polylactic acid fiber containing silver nanowires prepared in Preparation Example 9. Compared with Preparation Example 7 in Example 1, Preparation Example 9 does not add cetylpyridinium bromide. The radial and weft breaking strengths of the clothing fabric prepared in Example 4 are both reduced, and the other properties do not change significantly.

[0071] In Example 5, the polylactic acid fiber containing silver nanowires prepared in Preparation Example 10 was used. Compared with Example 1, nanocellulose and cetylpyridinium bromide were not added to the polylactic acid fiber containing silver nanowires in Preparation Example 10. It can be seen from the data comparison in Table 1 that the breaking strength of the clothing fabric prepared in Example 5 is significantly reduced.

[0072] Compared with Example 1, Example 6 uses the electrospun fibers of polyacrylonitrile and polyurethane prepared in Preparation Example 13. Compared with Preparation Example 11, Preparation Example 13 does not add nano zinc oxide. It can be seen that the breaking strength of the prepared clothing fabric is reduced, the wrinkle recovery angle is reduced, the tensile fracture resistance and anti-wrinkle effect are weakened, and the initial antibacterial ability is reduced.

[0073] In Example 7, electrospun fibers of polyacrylonitrile and polyurethane prepared in Preparation Example 14 were used. Compared with Preparation Example 11, Preparation Example 14 used deionized water instead of the base liquid, that is, the base liquid was not added with chitosan. Compared with Example 1, the antibacterial ability of the prepared clothing fabric decreased, and after washing 50 times, the antibacterial rate decreased more significantly, the breaking strength decreased, and the wrinkle recovery angle decreased significantly.

[0074] Compared with Example 1, the electrospun fibers of polyacrylonitrile and polyurethane in Example 8 were made from Preparation Example 15, in which no nano zinc oxide, chitosan or penetrant was added. The data in Table 1 showed that the breaking strength of the clothing fabric prepared in Example 8 decreased, the initial antibacterial effect decreased, the antibacterial rate decreased more after multiple washings than in Example 1, and the wrinkle recovery was reduced.

[0075] In Comparative Example 1, the modified cotton fiber prepared in Preparation Example 3 was used. In Preparation Example 3, the treatment liquid was not used for impregnation, and only the finishing liquid was used for treatment. The breaking strength of the clothing fabric prepared in Comparative Example 1 decreased, the wrinkle recovery angle decreased, the initial antibacterial rate decreased, the antibacterial ability weakened, and the difference in the decrease in the antibacterial rate after multiple washings increased, indicating that the treatment liquid can not only increase the antibacterial effect, but also improve the antibacterial durability.

[0076] In Comparative Example 2, compared with Example 1, the modified cotton fiber is made of Preparation Example 4. Compared with Preparation Example 1, no nylon waste silk is added to the treatment liquid. Compared with Example 1, it can be seen that the breaking strength and wrinkle recovery angle of the clothing fabric are reduced, and the antibacterial rate decreases significantly after washing, indicating that nylon waste silk can improve the tensile breaking strength of the fabric, increase the anti-wrinkle effect, and enhance the antibacterial durability.

[0077] In Comparative Example 3, the modified cotton fiber prepared in Preparation Example 5 was used. Compared with Preparation Example 1, the finishing liquid was not used for treatment, and only the treatment liquid was used for immersion. It can be seen that the initial antibacterial rate of the clothing fabric decreased, and the anti-wrinkle effect was weakened, indicating that the finishing liquid can improve the antibacterial properties of the cotton fiber and enhance its anti-wrinkle ability.

[0078] In Comparative Example 4, the modified cotton fiber prepared in Preparation Example 6 was used. Compared with Preparation Example 1, only titanium dioxide sol was used in the finishing liquid. It can be seen that although the antibacterial ability of the material is not much different from that of Example 1, its antibacterial durability is weakened.

[0079] In Comparative Example 5, electrospun fibers of polyacrylonitrile and polyurethane were not added, and in Comparative Example 6, electrospun fibers of polyacrylonitrile and polyurethane and polylactic acid fibers containing silver nanowires were not added. Only modified cotton fibers were used to prepare clothing fabrics. From the data in Table 1, it can be seen that the breaking strength of the clothing fabrics prepared in Comparative Examples 5 and 6 decreased, the wrinkle recovery angle decreased, the initial antibacterial rate weakened, and the decrease in the antibacterial rate was similar to that in Example 1.

[0080] In Comparative Example 7, the cotton fiber was not modified, and electrospun fibers of cotton fiber, polyacrylonitrile and polyurethane, and polylactic acid fibers containing silver nanowires were used as raw materials to prepare clothing fabrics. It can be seen that the initial antibacterial ability of the fabric was weakened. This specific embodiment is merely an explanation of the present application, and it is not a limitation of the present application. After reading this specification, those skilled in the art can make modifications to the present embodiment as needed without creative contribution, but as long as it is within the scope of the claims of the present application, it is protected by the patent law.

Claims

1. An antibacterial and wrinkle-resistant clothing fabric, characterized in that: The fabric includes modified cotton fiber, electrospun fiber of polyacrylonitrile and polyurethane, and polylactic acid fiber containing silver nanowires in a mass ratio of 1:0.1-0.3:0.3-0.5; The method for preparing the modified cotton fiber comprises the following steps: The cotton fibers are dipped in a finishing liquid, dried, and shaped to obtain pretreated cotton fibers; The pretreated cotton fiber is immersed in a treatment solution, and then dried and baked to obtain modified cotton fiber; The finishing liquid comprises the following raw materials in parts by weight: 4-4.5 parts of citric acid modified titanium dioxide sol, 0.1-0.3 parts of sodium hypophosphite, 0.1-0.3 parts of triethanolamine, and 4.9-5.8 parts of deionized water; The treatment liquid comprises the following raw materials in parts by weight: 7.4-8.1 parts of nylon waste silk, 1.5-2.5 parts of chitosan quaternary ammonium salt, 52.6-59.4 parts of N,N-dimethylformamide and 40-45 parts of alkaline silica sol.

2. The antibacterial and wrinkle-resistant clothing fabric according to claim 1, characterized in that: The preparation method of the polylactic acid fiber containing silver nanowires is as follows: Dispersing nanocellulose in deionized water to form a suspension with a concentration of 4-6 wt %; Adding silver nanowires to the suspension, adding cetylpyridinium bromide, stirring for 5-10 minutes, filtering and drying to obtain modified silver nanowires; The polylactic acid slices are dried and evenly mixed with the modified silver nanowires, and melt-spun to obtain polylactic acid fibers containing silver nanowires.

3. The antibacterial and wrinkle-resistant clothing fabric according to claim 2, characterized in that: The mass ratio of the silver nanowires to the polylactic acid slices is 0.1-0.2:1; The mass ratio of the silver nanowires, nanocellulose and cetylpyridinium bromide is 1:0.8-1:0.6-1.

4. The antibacterial and wrinkle-resistant clothing fabric according to claim 1, characterized in that: The electrospun fibers of polyacrylonitrile and polyurethane are prepared by the following method: Add polyacrylonitrile to DMF, stir and dissolve to obtain a base solution with a concentration of 10 wt%, add polyurethane, stir and dissolve to obtain a spinning solution; The spinning solution is subjected to electrospinning and vacuum drying for 10-12 hours to obtain a nanofiber membrane; The chitosan is dissolved in an acetic acid solution to prepare a base solution with a concentration of 1-1.5 wt %, and a penetrant and nano zinc oxide are added to the base solution, and ultrasonicated for 10-20 minutes to prepare an impregnation solution; The nanofiber membrane is placed in the impregnation solution, dipped and rolled twice, with a rolling rate of 80-85%, and dried at 75-80°C.

5. The antibacterial and wrinkle-resistant clothing fabric according to claim 4, characterized in that: The mass ratio of polyacrylonitrile to polyurethane is 2.5-3:1; The mass ratio of the chitosan, the penetrant and the nano zinc oxide is 1:0.1-0.5:1-2.

6. The antibacterial and wrinkle-resistant clothing fabric according to claim 1, characterized in that: The penetrant is selected from at least one of sodium alkyl sulfonate, sodium secondary alkyl sulfate, sodium isooctyl polyoxyethylene ether phosphate, sulfated castor oil, and phosphate compounds.

7. The antibacterial and wrinkle-resistant clothing fabric according to claim 1, characterized in that: The preparation method of the citric acid modified titanium dioxide sol is as follows: by weight, 1-2 parts of citric acid, 13-16 parts of anhydrous ethanol and 1-2 parts of butyl titanate are mixed evenly to prepare solution A, and 6-12 parts of deionized water, 0.075-0.15 parts of concentrated hydrochloric acid and 7-8 parts of anhydrous ethanol are mixed evenly to prepare solution B; Solution B was added into solution A and stirred evenly at room temperature to obtain a citric acid-modified titanium dioxide sol.

8. The antibacterial and wrinkle-resistant clothing fabric according to claim 1, characterized in that: The rolling rate of the finishing liquid is 70-75%, the drying temperature is 50-55°C, the drying time is 3-5min, the setting temperature is 150-160°C, and the setting time is 3-5min; The processing liquid has a rolling rate of 80-85%, a drying temperature of 50-55° C., a drying time of 3-5 minutes, a baking temperature of 120-130° C., and a baking time of 3-5 minutes.

9. The method for preparing the antibacterial and wrinkle-resistant clothing fabric according to any one of claims 1 to 8, characterized in that: The following steps are involved: The modified cotton fiber, electrospun fiber of polyacrylonitrile and polyurethane and polylactic acid fiber containing silver nanowires are mixed, carded, drawn, roved, spun, wound and woven to make fabrics.

10. The method for preparing the antibacterial and wrinkle-resistant clothing fabric according to claim 9, characterized in that: During weaving, the warp yarn count is 150-180 needles / cm, the weft yarn count is 200-220 needles / cm; the warp knitting speed is 600-800m / min, the fabric thickness is 0.5-1.5mm, and the gram weight is 50-300g / m 2 .

Citation Information

Cited By

  • Mildew-proof antibacterial composite material and preparation method thereof

    CN120096168A

  • Anti-yellowing lining cloth with hot melt coating and preparation method of anti-yellowing lining cloth

    CN120759093A

  • Preparation method of antibacterial and antiviral degradable bacterial grass fiber blended yarn material

    CN122649241A